Influence of Total Asset, Working Capital and Cash Flow with Net Profit as Mediation on Stock Price of Plastics and Packaging Industry Sub-Sector in Indonesia Stock Exchange - Ali Akbar (Dinasti Publisher, 2025)
The aim of this research is to determine and analyze influence of Total Asset, Working Capital and Cash Flow with Net Profit as mediate variable on Stock Price at Plastics and Packaging industry sub-sector on the Indonesian stock exchange. Annual reports and closing Stock Price used on this research as secondary data. Sample of data using Plastic and Packaging industry sub-sector on the Indonesia Stock Exchange for the period 2016-2022. Sampling method been using purposive sampling. Path analysis with SPSS software used for this research to analyzing data. The sampling method uses purposive sampling. Research results: 1) The direct effect of Total Asset, Working Capital and Cash Flow on Stock Price are greater than the indirect effect of Total Asset, Working Capital and Cash Flow through Net Profit on Stock Price. 2) Total Asset, Working Capital and Cash Flow simultaneously have significant effect on Net Profit. 3) Partially Total Asset has positive and significant effect on Net Profit, Working Capital has positive and insignificant effect on Net Profit and Cash Flow has positive and significant effect on Net Profit. 4) Total Asset, Working Capital and Cash Flow simultaneously have significant effect on Stock Price. 5) Partially Total Asset has positive and significant effect on Stock Price, Working Capital has positive and insignificant effect on Stock Price and Cash Flow has positive and significant effect on Stock Price. 6) Net Profit has positive and significant effect on Stock Price.